Armed Movements and Counterinsurgency in Contemporary Mexico - Gaussens, Pierre (PARTECIPAZIONE E CONFLITTO, 2020)
Based on a case study, this article seeks to analyze the contemporary evolution of the armed movements in the southern Mexican state of Guerrero and the counterinsurgency operations they have faced. To reach this goal, the object of the qualitative methodology is the local history of a municipality, Ayutla de los Libres, from 1998 to 2013, describing the socio-political processes that were developed there and that separate both dates, each marked by a critical episode of repression. The main result is that, although the field of armed movements underwent great changes, moving from offensive to defensive forms, the counterinsurgency used against them shows strong continuities focused on repression.